2020
DOI: 10.1111/ics.12647
|View full text |Cite
|
Sign up to set email alerts
|

Perceived age and perceived health among a Chinese cohort: Does it mean the same thing?

Abstract: Background & Aims Previous investigations have aimed at investigating parameters affecting age perception on several ethnicities. Perceived health has been a newer focus on Caucasian skin, yet little is known on the skin features used to estimate the health status of Chinese women and we aimed to investigate whether these cues are the same as those used for age perception. Methods Age and health appearance of 276 Chinese female volunteers were estimated from their photographs by 1025 female naïve Chinese grade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Some skin features were specific to age perception (eg, eye bags, eye lid sagging, wrinkles), while others were rather related to health perception, such as pigmented spots, acne, scars, or skin hydration. 123 …”
Section: Emotional Balance/stressmentioning
confidence: 99%
“…Some skin features were specific to age perception (eg, eye bags, eye lid sagging, wrinkles), while others were rather related to health perception, such as pigmented spots, acne, scars, or skin hydration. 123 …”
Section: Emotional Balance/stressmentioning
confidence: 99%
“…In these circumstances, parents are obligated to be assessed their perception of their children's OHRQoL [16]. It was found that those persons belonging to higher age groups tend to perceive their own or their family health in a significantly more positive fashion than members of younger adult age groups [17,18]. This study is the first that specifically examined the relationship between the maternal age group with the OHRQoL of their children.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, different applications of artificial intelligence (AI), such as computer vision and machine learning algorithms, have been utilized in the cosmetics industry for the automated detection and analysis of image-based data, mostly as a face skin diagnostic tool [17,18,19]. In those assessments, the AI was validated by parallel assessments conducted by expert dermatologists, who normally use validated scales for skin ageing assessment.…”
Section: Hair Assembly Properties and Artificial Intelligencementioning
confidence: 99%